Helicobacter pylori and chronic kidney disease: controversy and possibility - Nasrat, Abdullah M.; Alhamad, Faisal F.; Alshammari, Ali Z. A. M.; Alnefaie, Zayed M.; Alsaedi, Yousef M.; Alshammari, Nafesa M.; Ahmed, Hassan A. A.; Aljohani, Ibrahim S. (International Journal Of Community Medicine And Public Health, 2025)
Chronic kidney disease (CKD) is rapidly increasing worldwide, constituting a major public health burden that will stress healthcare systems in all countries, with end-stage renal disease (ESRD) emerging as a growing challenge, particularly in developing nations. The increasing burden of CKD, coupled with limited financial and epidemiological resources in less developed countries, places a severe strain on existing health policies. Hypertensive illness and diabetes mellitus (DM) are significant predisposing risk factors for the development and progression of chronic kidney disease. However, the literature lacks sufficient knowledge about the influence of Helicobacter pylori on chronic kidney disease, and while there is controversy surrounding the association of H. pylori with DM and hypertension, current knowledge does not support a direct role of H. pylori in causing CKD. This prospective case series, conducted in Medina, Saudi Arabia, from October 2023 to October 2024, involved nine patients with varying grades of renal dysfunction associated with the presence of H. pylori, which was confirmed through specific tests; colon clearing was performed on all patients. The results indicated a marked improvement in kidney function, highlighted by decreased blood urea and serum creatinine levels. Consequently, colonic H. pylori strains could be a hidden contributor to CKD through toxic or immune mechanisms, suggesting that careful attention to colonic health may be crucial for individuals with impaired kidney function associated with H. pylori existence.